Programa Sesc de esportes e educação de jovens na Região de Itaquera, município de São Paulo - SP - Pereira, Beatriz Souza (2024)
The participation of adolescents from peripheral areas of Itaquera, in the East Area of São Paulo City, in the Sesc Sports Program (PSE) affects the comprehensive development of this age group. The indicators that characterize this experience extend beyond the sports motor repertoire, encompassing the socio-educational significance of the activities conducted, considering the particularities of the region. The objective of this research is to investigate the conceptions of the Sesc Sports Program (PSE) in identifying its repercussions on the lives of young people who participate in the sports activity groups, with the purpose of highlighting the importance of the principles and values of the Program and the transformative potential of its actions. The study was developed considering theoretical approaches related to the concept of education and curriculum, with references to authors such as Paulo Freire, Edgar Morin, Branca Ponce, and Maria da Glória Gohn. Reflections on the relationship between education and sports are based on the works of Mauro Betti concerning the pedagogy of sports. Itaquera, the locus of the investigations, stands out for the implementation of formal and non-formal education modalities, considering their articulation with sports practice in the community. The research methodology, based on a qualitative approach, includes: bibliographic study, document analysis as procedures and field research involving participants and alumni of the Sesc Sports Program (PSE), between 2014 and 2023. Data collection was conducted through interviews using a semi-structured script, consisting of closed and open questions. The data analysis is grounded in the theoretical-conceptual foundation relevant to the fields of Education and Sports, the research objectives as its guiding principles, considering its contribution to the uniqueness of the locus defined for the research